Ever-green Vietnamese : super-fresh recipes, starring plants from land and sea - Nguyen, Andrea Quynhgiao (Ten Speed Press, 2023)
"Plant-based cooking meets the dynamic flavors of Vietnamese cuisine in these 100+ vegetable-driven recipes"--